Dietary Intake of Fatty Acids and Cholesterol in Housewives - YOSHIDA, Ayako; SUMIMOTO, Tatsuo; TANAKA, Ryoichi (Nihon Eiyō, Shokuryō Gakkai shi, 1986)
A duplicate portion study for 7 days was made on dietary intake of fat, fatty acids and cholesterol in 6 housewives from 32 to 38 years old living in Osaka Prefecture. 1. The average daily intake of fat was approximately 50g in 5 subjects and was 40.8g in the other. 2. The average daily intake of cholesterol was from 350 to 400mg in 3 subjects and was approximately 500mg in the others. No relation was observed between fat intake and cholesterol intake. 3. The major component in the total fatty acids was C18:1 in all the subjects, and the second. major one was C18:2 (5 subjects) or C16:0 (1 subject). Mono-unsaturated fatty acids comprised from 40 to 47% of the total fatty acids in all subjects. The proportion of C20:5 (0.2%) or C22:6 (0.5%) to the total fatty acids showed a small difference among the subjects. 4. The ratios of total poly-unsaturated fatty acids to saturated fatty acids (P/S ratios) varied daily in a week. The average P/S ratio was approximately 1.0 in 5 subjects and was O. 7 in the other one. 5. The results by the duplicate portion study were compared with those by the market basket study based on the “National Nutrition Survey in Osaka. ” The fat intake and the P/S ratio were almost similar to each other, while, the cholesterol intake and the proportion of monounsaturated fatty acids to the total fatty acids were larger in the former results than in the latter.